Ender's game - Card, Orson Scott (New York : TOR, 1994)
Young Ender Wiggin may prove to be the military genius Earth needs to fight a desperate battle against a deadly alien race that will determine the future of the human race.
"A Tom Doherty Associates book.".
Sequel: Speaker for the Dead.
Adult
Keywords: Military education -- Fiction; Space warfare -- Fiction; Wiggin, Ender (Fictitious character) -- Fiction; Military education -- Fiction; Science fiction; Space warfare -- Fiction; Wiggin, Ender (Fictional character) -- Fiction; Science fiction